Identification of novel cis‐elements bound by BplMYB46 involved in abiotic stress responses and secondary wall deposition. Issue 10 (15th July 2018) - Guo, Huiyan; Wang, Liuqiang; Yang, Chuanping; Zhang, Yiming; Zhang, Chunrui; Wang, Chao
Abstract: Transcription factors (TFs) play vital roles in various biological processes by binding to cis ‐acting elements to control expressions of their target genes. The MYB TF BplMYB46, from Betula platyphylla, is involved in abiotic stress responses and secondary wall deposition. In the present study, we used a TF‐centered yeast one‐hybrid technology (TF‐centered Y1H) to identify the cis ‐acting elements bound by BplMYB46. We screened a short‐insert random library and identified three cis ‐elements bound by BplMYB46: an E‐box (CA(A/T/C)(A/G/C)TG) and two novel motifs, a TC‐box (T(G/A)TCG(C/G)) and a GT‐box (A(G/T)T(A/C)GT(T/G)C). Chromatin immunoprecipitation (ChIP) and effector‐reporter coexpression assays in Nicotiana tabacum confirmed binding of BplMYB46 to the TC‐box, GT‐box, and E‐box motifs in the promoters of the phenylalanine ammonia lyase ( PAL ), peroxidase ( POD ), and superoxide dismutase ( SOD ) genes, which function in abiotic stress tolerance and secondary wall biosynthesis. This finding improves our understanding of potential regulatory mechanisms in the response to abiotic stress and secondary wall deposition of BplMYB46 in B. platyphylla . Abstract : The novel cis ‐elements bound by BplMYB46 were found by using a transcription factor‐centered yeast one‐hybrid technology. These binds were further proved by chromatin immunoprecipitation and effector‐reporter co‐expression assays. This finding revealed the potential regulatory mechanisms of BplMYB46 in B.platyphylla .